Neuro-linguistic Programming in the English Classroom: Perceptions and Applications Among Teachers - Siti Aisyah Ginting; Rita Hartati (VELES Voices of English Language Education Society, 2023)
This study investigates the perceptions and practices of Neuro-Linguistic Programming (NLP) techniques among English as a Foreign Language (EFL) teachers, exploring their impact on communication skills and subject comprehension. The research focuses on eight key factors within NLP: flexibility, anchoring, elicitation, modeling, individual differences, leadership, building a relationship, and emotional and cognitive boosters. A sample of 20 EFL teachers in Medan, Indonesia, participated in this descriptive qualitative study, responding to a survey questionnaire adapted from previous research. The findings highlight a consensus among educators, showcasing their recognition of NLP's applicability and effectiveness across these factors. Teachers exhibit a strong commitment to student-centered pedagogy, emphasizing personalized interaction and visual learning experiences through board-based teaching methods. While the study acknowledges certain limitations, such as a small sample size and reliance on self-reported perceptions, it provides valuable insights for further research. Future studies can expand on these findings to explore NLP's influence on student outcomes and address potential implementation challenges.